Molecular-frame measurements of light-induced processes using rotational coherences driven by ultrafast laser pulses - Lam, Huynh Van Sa (Kansas State University, 2021)
One of the main goals of ultrafast atomic, molecular, and optical physics is to monitor and control chemical reactions in real time. Ultrashort laser pulses (time scales in picoseconds or shorter) provide sufficiently high spatio-temporal resolution to study the reaction dynamics. Together with the development of shorter pulses, studies of these reactions in three-dimensional (3D) space are also crucial since the 3D structures determine the physical and chemical properties of molecules. For example, stereoisomers, such as chiral molecules, have the same molecular formula but can behave very differently in reactions with other stereoisomers or optical pulses because of the different orientations of their atoms in space. However, in a gas-phase experiment, the orientation-dependent information is usually lost after averaging over a randomly distributed molecular sample. Many different methods have been investigated to solve this important problem. In 2014, Makhija et al. demonstrated that the angle-dependent strong-field ionization of ethylene (C₂H₄), an asymmetric top molecule, can be retrieved from a time-resolved measurement of the yield of the cation. In this pump-probe experiment, the pump aligns and the probe ionizes the molecules, and the ion yield is measured as a function of pump-probe delay. The angle dependence is retrieved from fitting to this delay-dependent ion yield. This time-domain approach, called Orientation Resolution through Rotational Coherence Spectroscopy (ORRCS), has many advantages that can be exploited in other applications. The main theme of this work is the further development of ORRCS for extracting orientation-resolved information of different processes from rotational wave packet dynamics. The first goal of this dissertation is to systematically investigate and develop the ORRCS retrieval algorithm, since the retrieval of the angle dependence is sensitive to many parameters. We perform a series of experiments and statistical analyses to evaluate different types of errors, determine the appropriate size of the model, and check the consistency of the retrieval. Specifically, we look at the angle-dependent strong-field ionization of carbon dioxide (CO₂, a linear molecule) and sulfur dioxide (SO₂, an asymmetric top molecule). Strong-field ionization of CO₂ has been discussed extensively in the literature because there were significant discrepancies between different experiments and theories, while SO₂ has been used extensively in other experiments. The second goal of this dissertation is to expand the time-domain approach to momentum measurements. With this new development, we present two applications of ORRCS to the dissociation and photoionization of molecules. In the dissociation of molecules, the axial recoil approximation is often used without validation. We show that this approximation can be tested by measuring the momentum distributions of the fragment ions as a function of pump-probe delay. In particular, we examine the dissociation of CO₂ and N₂ with 800 nm and 262 nm laser pulses, respectively. In each case, we determine how the likelihood of dissociation depends on the initial orientation of the molecule and the effect of the laser field on the momentum distribution of the fragment ions. With a similar framework but different interpretation, we show that substantial information about molecular-frame photoelectron angular distributions can be obtained using rotational wave packets. We retrieve the alignment dependence of photoelectron angular distributions from N₂, CO₂, and C₂H₄ in the few-photon ionization regime. We also compare few-photon ionization with single-photon ionization and strong-field ionization to enrich our knowledge in this regime, which is not very well understood. We believe that the time-domain approach discussed in this work is useful in many areas of ultrafast physics and chemistry. With the rapid development of high-repetition-rate light sources in recent years, we expect that many measurements, including those using x-ray free-electron lasers and ultrafast electron beams, will have the ability to apply our method and gain valuable insights into molecular structures and dynamics in the near future.
Keywords: Molecular frame; Strong-field ionization; Laser-induced dissociation; Rotational coherences; Photoelectron angular distributions; Laser-induced molecular alignment